Zero-valent iron microspheres coated with electron shuttles on surfaces and application of zero-valent iron microspheres
By coating agarose and AQDS nano zero-valent iron microspheres, the electron shuttle body is used to regulate contactless electron transfer, the problem of low degradation efficiency of nano zero-valent iron in groundwater is solved, and stability and activity are achieved The balance of the problem improves pollutant repair efficiency and reduces costs.
Patent Information
- Application Number
- CN202411282572.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-13
AI Technical Summary
In practical applications, nano zero-valent iron has problems with passivation layer formation, aggregation and pH sensitivity, resulting in a reduction in repair efficiency. The existing modification solutions cannot take into account both stability and activity.
By coating nano zero-valent iron with agarose and AQDS, the electron shuttle is used to regulate contactless electron transfer, enhance the generation efficiency and distance of ROS, and realize indirect contact oxidation and degradation of pollutants.
It improves the pollutant degradation efficiency of nano zero-valent iron in groundwater, takes into account the stability and activity of the material, reduces costs, and has practicality and promotional value.
Smart Images

Figure CN119285076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental engineering and nanomaterials, and in particular relates to a zero-valent iron microsphere with an electron shuttle coated on its surface and application thereof. Background Art
[0002] With the acceleration of industrialization and urbanization, groundwater pollution has become increasingly prominent and has received widespread attention worldwide. Nano-zero-valent iron (nZVI) has received widespread attention in the process of groundwater remediation due to its high removal efficiency for organic or heavy metal pollutants. It is generally believed that the reaction mechanism of nZVI in removing pollutants involves both direct electron transfer reduction and free radical oxidation processes. The reduction removal mechanism is that electrons are directly transferred from the nZVI surface to the pollutants; the oxidation removal mechanism is that under sufficient O2 conditions, the electrons of nZVI can be captured by O2 absorbed on the surface to produce highly active and highly oxidizing reactive oxygen species (ROS) to remove pollutants. However, nZVI has several disadvantages in practical applications: (1) When nZVI comes into contact with oxygen, a passivation layer (such as magnetite, goethite, and scaly bluestone) will be produced on the surface, which prevents the internal Fe from being removed. 0 Direct contact with external pollutants reduces the repair efficiency of nZVI. (2) nZVI particles are easily aggregated due to their own magnetism and surface tension, which causes their reaction activity to drop rapidly; (3) The repair efficiency of nZVI is greatly affected by pH and is prone to passivation under alkaline conditions. In response to the above shortcomings, the existing solution is to use polymers, polyelectrolytes and surfactants to add a coating layer to the surface of nZVI to protect nZVI from the influence of O2 and reduce the passivation and aging of nZVI, but it will also mask some active sites, resulting in slower electron transfer and reduced reactivity. Some activity is sacrificed in exchange for stability, and the stability and activity of nZVI materials cannot be taken into account. Summary of the invention
[0003] The purpose of the embodiments of the present application is to address the problems existing in the prior art and to provide a zero-valent iron microsphere with a surface-coated electron shuttle and its application, which can be applied to environmental pollution control, especially in groundwater and soil remediation, by regulating the non-contact transfer of nZVI electrons to enhance the ROS generation efficiency and extend the ROS generation distance, thereby achieving non-direct contact oxidative degradation of pollutants.
[0004] According to a first aspect of an embodiment of the present application, there is provided a zero-valent iron microsphere with a surface coated with an electron shuttle, wherein nano-zero-valent iron is coated with agarose containing the electron shuttle;
[0005] The zero-valent iron microspheres are prepared by a reverse suspension method, and the preparation process includes:
[0006] (1) Add Span 80 to mineral oil and mix well under heating to obtain a dispersant;
[0007] (2) uniformly mixing nano-zero-valent iron into a hot agarose solution containing an electron shuttle, dropping the mixed product into the preheated dispersant, mechanically stirring until completely emulsified and dispersed, naturally cooling to room temperature, and separating the zero-valent iron microspheres coated with the electron shuttle and the dispersant under the action of an external magnetic field;
[0008] (3) The zero-valent iron microspheres coated with electron shuttles are washed with anhydrous ethanol and then freeze-dried.
[0009] Furthermore, in step (1), the ratio of Span 80 to mineral oil is 1 g:25 ml.
[0010] Furthermore, in step (2), sodium anthraquinone-2,6-disulfonate is used to provide an electron shuttle, and the ratio of nano zero-valent iron to sodium anthraquinone-2,6-disulfonate is 5g:2L.
[0011] According to a first aspect of an embodiment of the present application, there is provided an application of zero-valent iron microspheres having a surface coated with electron shuttles as described in the first aspect in pollutant degradation.
[0012] Furthermore, the application is specifically as follows: placing zero-valent iron microspheres with electron shuttles coated on the surface in groundwater, and non-contactly regulating the redox reaction between nano zero-valent iron and pollutants through the electron shuttles to generate active oxygen and repair groundwater pollution.
[0013] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0014] It can be seen from the above embodiments that the present application provides a zero-valent iron microsphere with a surface coated electron shuttle, which can regulate the non-contact generation of ROS by nZVI through the electron shuttle. Through this method, the output and distance of the non-contact generation of ROS by nZVI can be accurately regulated, thereby proposing its application in pollutant degradation. Based on this principle, the present application synthesized and evaluated the ability of nZVI materials to produce ROS and oxidatively degrade pollutants before and after AQDS-agarose modification. It was verified that under redox fluctuation conditions, AQDS can regulate the electron transfer efficiency of nZVI materials in groundwater media, thereby enhancing the ability of nZVI to produce ROS non-contactly. The present application provides a modification strategy that takes into account the stability and activity of nZVI materials, improves the efficiency of groundwater pollution remediation, and reduces its cost, and has strong practicality and promotion value.
[0015] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0017] Figure 1 The figure shows the synthesis, characterization and performance evaluation of the nZVI@agarose / AQDS composite material according to an exemplary embodiment, wherein (a) is a schematic diagram of the material synthesis process; (b) is a material characterization diagram, (c) is the material's ability to produce ·OH, and (d) is the material's efficiency in degrading BPA.
[0018] Figure 2 It is a schematic diagram of the principle and reaction device for regulating the non-contact generation of ROS by nZVI using the electron shuttle AQDS according to an exemplary embodiment, wherein (a) is a reaction mechanism diagram of AQDS-mediated non-contact generation of ROS by nZVI, (b) is a three-layer reaction device diagram for measuring the non-contact generation of ROS by nZVI, and (c) is a sample photo of AQDS-enhanced nZVI generation of ROS at different control distances.
[0019] Figure 3 The present invention is a qualitative and quantitative analysis of the non-contact generation of ROS by nZVI regulated by the electron shuttle AQDS according to an exemplary embodiment, wherein (a) is the reduction of AQDS by nZVI at different distances to generate reduced AQH2DS, (b) is the EPR signal of the production of semiquinone radicals and ·OH by non-contact electron transfer by nZVI, and (c) is the quantitative determination of the enhancement of ROS generation by nZVI by AQDS at different distances. DETAILED DESCRIPTION
[0020] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0021] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0022] It should be understood that although the terms first, second, third, etc. may be used in the present application to describe various information, these information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Depending on the context, the word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining".
[0023] The present invention provides a zero-valent iron microsphere with a surface coated with an electron shuttle, wherein nanometer zero-valent iron is coated with agarose containing the electron shuttle in the zero-valent iron microsphere;
[0024] The zero-valent iron microspheres are prepared by a reverse suspension method, such as Figure 1 As shown in (a), the preparation process includes:
[0025] (1) Add Span 80 to mineral oil and mix well under heating to obtain a dispersant;
[0026] Specifically, 1.0 g of Span 80 was weighed as an emulsifier, added to 25 mL of mineral oil, and heated and stirred.
[0027] (2) uniformly mixing nano-zero-valent iron into a hot agarose solution containing an electron shuttle, dropping the mixed product into the preheated dispersant, mechanically stirring until completely emulsified and dispersed, naturally cooling to room temperature, and separating the zero-valent iron microspheres coated with the electron shuttle and the dispersant under the action of an external magnetic field;
[0028] Prepare a 2% mass fraction hot agarose solution, weigh 250 mg nZVI and add it to 10 mL hot agarose solution containing anthraquinone-2,6-disulfonic acid sodium (AQDS), stir evenly; then slowly drop it into the preheated dispersant, mechanically stir until completely emulsified and dispersed, cool naturally to room temperature, and separate the nZVI@agarose / AQDS microspheres and the dispersant under the action of an external magnetic field.
[0029] (3) washing the zero-valent iron microspheres coated with the electron shuttle with anhydrous ethanol and then freeze-drying them;
[0030] The nZVI@agarose / AQDS microspheres were washed three times with anhydrous ethanol and transferred to a freeze dryer for freeze drying, and then transferred to a glove box for standby use.
[0031] By introducing anthraquinone-2,6-disulfonate sodium (AQDS), a class of artificially synthesized quinone model compounds, as a redox mediator to accelerate the electron transfer of nZVI when synthesizing nZVI materials coated with agarose on the surface, the stability and activity of the nZVI material can be simultaneously improved.
[0032] Figure 1 is a diagram showing the synthesis, characterization and performance evaluation of nZVI@agarose / AQDS material according to an exemplary embodiment. The synthesis process of nZVI@agarose / AQDS material is shown in FIG. Figure 1 As shown in (a), first, 25 mL of mineral oil and 1 g of Span 80 were used as dispersants, stirred and mixed in a beaker and preheated to 90°C. Subsequently, 250 mg of nZVI material was weighed and placed in 10 mL of hot agarose solution (2 wt%), stirred and mixed, and then added dropwise to the dispersant. The mixture was fully emulsified for 20 min under mechanical stirring, and then naturally cooled to room temperature. The dispersant phase was removed under the action of an external magnetic field, and 25 mL of ethanol was added to fully stir and dissolve the residual dispersant. After washing for 3 times, the mixture was transferred to a freeze dryer for freeze drying. The synthesized nZVI@agarose / AQDS microspheres (such as Figure 1 (b) in the figure shows that the particle size distribution is between 10-100μM. Elemental scanning analysis shows that in addition to Fe, C, N, O, S, etc. are distributed on the surface of the material, indicating that a layer of agarose / AQDS is successfully coated evenly on the surface of nZVI. In addition, the OH production capacity and the efficiency of degrading bisphenol A (BPA) in groundwater of nZVI@agarose and nZVI@agarose / AQDS materials were compared. The material concentration used in the reaction system was 1g / L, and the initial BPA concentration was 1μM. At the same time, the material was tested by adding 1mM TPA. · The accumulation of OH. Figure 1 (c) and Figure 1 As shown in (d), the efficiency of nZVI@agarose material in producing ·OH is low and it cannot effectively degrade BPA. On the contrary, the efficiency of nZVI@agarose / AQDS material in producing ·OH is significantly increased and it can effectively degrade BPA, proving that AQDS can enhance the reactivity of surface-coated nZVI and achieve the goal of simultaneously improving the stability and reactivity of nZVI.
[0033] The present invention also provides an application of the zero-valent iron microspheres with the surface coated with electron shuttles in pollutant degradation, specifically: the zero-valent iron microspheres with the surface coated with electron shuttles are placed in groundwater, and the electron shuttles are used to non-contactly regulate the redox reaction between the nano zero-valent iron and the pollutants to generate active oxygen and repair the groundwater pollution.
[0034] First, the principle that nZVI@agarose / AQDS microspheres can degrade pollutants is explained and proved.
[0035] like Figure 2As shown in (a), the application in principle utilizes the electron shuttle property of AQDS, first accepting electrons from the surface of nZVI under anaerobic conditions, reducing to generate AQH2DS, and then AQH2DS migrates and diffuses as an electron carrier, and then transfers electrons to O2 under aerobic conditions to generate ROS. AQH2DS itself is oxidized and returns to AQDS, completing the electron transfer. The present invention uses a three-layer reactor for detecting non-contact ROS production under redox fluctuations, including a lower layer of nZVI as an electron donor, a middle layer of agarose solidified layer simulating groundwater medium, and an upper layer of liquid for ROS quantitative analysis. In one embodiment, as Figure 2 As shown in (b), a 20 mL crimp bottle is used as a reaction container. First, agarose is used to wrap and fix nZVI so that it cannot move in space (to facilitate the subsequent determination of ROS production at different distances). Secondly, a layer of agarose gel (2wt%, groundwater) containing 1mM AQDS is added to the upper layer of nZVI. The thickness of the electron transfer medium layer is controlled by the volume of the added agarose gel. After it is cooled and solidified, it is transferred to a glove box and covered with a layer of oxygen-free groundwater containing 1mM AQDS. Specifically, first, agarose is suspended in groundwater at a mass concentration of 2% and melted by microwave. The hot agarose solution is kept at a constant temperature of 55°C in a constant temperature water bath before use. After 50 g / L of nZVI material and agarose solution (55°C) are vigorously shaken and mixed evenly, 1.0 mL of the nZVI-agarose mixture is poured into a transparent glass headspace crimp bottle to prepare the nZVI electron donor layer. After it is completely solidified, pour different volumes of agarose solution containing anthraquinone-2,6-disulfonic acid sodium (AQDS) as the medium layer and solidify it on the nZVI electron donor layer. Finally, put the sample into a glove box (100% N2) and inject 3.0mL of groundwater (containing AQDS) into the bottle to carry out electron diffusion reaction under anaerobic conditions. After a certain period of electron diffusion, collect the overlying groundwater and add the ROS probe for aerobic exposure to detect ROS production. The reaction system is set at different distances as follows Figure 2 As shown in (c) in the figure, a ruler is used to quantify the thickness of the dielectric layer in each reactor, which is the distance over which nZVI generates ROS.
[0036] like Figure 3 As shown in (a), AQDS generates reduced AQH2DS at different distances from nZVI. AQH2DS is a deep red solution. The UV-visible absorption spectrum shows that it has a maximum absorption at a wavelength of 405nm. As the thickness of the dielectric layer increases, the absorption at 405nm decreases, and the absorption at 330nm is higher (AQDS absorption peak), indicating that the farther away from nZVI, the lower the concentration of reduced AQH2DS. In order to verify the non-contact electron migration and the generation of ROS, the generation of semiquinone radicals and ·OH was measured using EPR, as shown in Figure 2. Figure 3As shown in (b), under anaerobic conditions, the electron paramagnetic resonance (EPR) signal of the semiquinone radical was detected in the solution of nZVI non-contact reduction of AQDS, indicating the existence of an electron transfer process from nZVI to AQDS. After the AQDS solution was reduced by nZVI (the solution was dark red), the aliquot was directly transferred to the capillary under anaerobic conditions and analyzed using a Bruker-ESR A300 EPR spectrometer. Subsequently, 20 mM of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) scavenger was added and exposed to oxygen. It was found that the red color of the solution faded, and the EPR signal of ·OH was detected, proving that AQH2DS was oxidized by O2 to produce ·OH. Specifically, as Figure 3 As shown in (c), TPA and fluorescent red / horseradish peroxidase were used as probes for ·OH and H2O2, respectively, to measure the ROS production generated by nZVI at different distances when 1 mM AQDS was added. After 24 hours of anaerobic reaction, at a distance of 2 mm from the nZVI material, the H2O2 production was 318 μM and the ·OH production was 1.26 μM. The farthest ROS generation distance could reach 10 mm.
[0037] In summary, the three-layer reactor was used to determine the yield of ROS generated by the nZVI material coated with agarose on the surface in groundwater in a non-contact manner; the electron transfer efficiency of the nZVI material coated with agarose on the surface was regulated by exogenous addition of AQDS, thereby enhancing the ability of nZVI to produce ROS in a non-contact manner. Based on this principle, the ability of nZVI to produce ROS and oxidatively degrade pollutants before and after AQDS-agarose modification was synthesized and evaluated. The results verified that under redox fluctuation conditions, AQDS can regulate the electron transfer efficiency of nZVI in groundwater media, thereby enhancing the ability of nZVI to produce ROS in a non-contact manner. The present invention provides a modification strategy that takes into account the stability and activity of nZVI, improves the efficiency of groundwater pollution remediation, and reduces its cost, and has strong practicality and promotion value.
[0038] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application.
[0039] It should be understood that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.
Claims
1. A zero-valent iron microsphere with an electron shuttle coated on its surface, characterized in that: In the zero-valent iron microspheres, nano-zero-valent iron is coated by agarose containing electron shuttles; The zero-valent iron microspheres are prepared by a reverse suspension method, and the preparation process includes: (1) Add Span 80 to mineral oil and mix well under heating to obtain a dispersant; (2) uniformly mixing nano-zero-valent iron into a hot agarose solution containing an electron shuttle, dropping the mixed product into the preheated dispersant, mechanically stirring until completely emulsified and dispersed, naturally cooling to room temperature, and separating the zero-valent iron microspheres coated with the electron shuttle and the dispersant under the action of an external magnetic field; (3) The zero-valent iron microspheres coated with electron shuttles are washed with anhydrous ethanol and then freeze-dried.
2. The zero-valent iron microspheres with surface-coated electron shuttles according to claim 1, characterized in that: In step (1), the ratio of Span 80 to mineral oil is 1 g:25 ml.
3. The zero-valent iron microspheres with surface-coated electron shuttles according to claim 1, characterized in that: In step (2), sodium anthraquinone-2,6-disulfonate is used to provide an electron shuttle, and the ratio of nano zero-valent iron to sodium anthraquinone-2,6-disulfonate is 5g:2L.
4. Use of zero-valent iron microspheres with surface-coated electron shuttles as claimed in any one of claims 1 to 3 in pollutant degradation.
5. The use according to claim 4, characterized in that: The application is specifically as follows: placing zero-valent iron microspheres with electron shuttles coated on the surface in groundwater, and using the electron shuttles to non-contactly regulate the redox reaction between nano zero-valent iron and pollutants to generate active oxygen and repair groundwater pollution.
Citation Information
Patent Citations
Organic wastewater treatment method based on polyaniline coated nanometer zero-valent iron
CN104310566A
Method for in-situ remediation of organochlorine contaminated soil by combining zero-valent iron with indigenous microorganisms
CN110303039A
Method for sequentially anaerobically and aerobically efficiently degrading soil PAHs (polycyclic aromatic hydrocarbons) and DDTs (diDTs) combined pollution by combined reinforced microorganisms
CN115041519A
Organic pollutant treatment system and application thereof
CN117125801A
Method for in-situ characterization of nano zero-valent iron electron migration distance
CN117309936A